On the Gl(2n) Eigenvariety: Branching Laws, Shalika Families and P-Adic L-Functions - Barrera-Salazar, D (Association for Mathematical Research, 2025)
In this paper, we prove that a GL(2n)-eigenvariety is étale over the (pure) weight space at non-critical Shalika points, and construct multi-variable p-adic L-functions varying over the resulting Shalika components. Our constructions hold in tame level 1 and Iwahori level at p, and give p-adic variation of L-values (of regular algebraic cuspidal automorphic representations of GL(2n) admitting Shalika models) over the whole pure weight space. In the case of GL(4), these results have been used by Loeffler and Zerbes to prove cases of the Bloch–Kato conjecture for GSp(4). Our main innovations are: (a) the introduction and systematic study of ‘Shalika refinements’ of local representations of GL(2n), and evaluation of their attached local twisted zeta integrals; and (b) the p-adic interpolation of representation-theoretic branching laws for GL(n) × GL(n) inside GL(2n). Using (b), we give a construction of multi-variable p-adic functionals on the overconvergent cohomology groups for GL(2n), interpolating the zeta integrals of (a). We exploit the resulting non-vanishing of these functionals to prove our main arithmetic applications. © 2025 Daniel Barrera Salazar, Mladen Dimitrov, Andrew Graham, Andrei Jorza and Chris Williams.